2022
DOI: 10.1038/s41598-022-07864-3
|View full text |Cite
|
Sign up to set email alerts
|

Study on the risk of soil heavy metal pollution in typical developed cities in eastern China

Abstract: Enrichment of heavy metals in urban soils has become a major regional environmental risk. At present, research on the soil heavy metals in cities lacks risk spatial correlation analyses between different heavy metals, and there is a relative lack of assessments of the ecological and health risks. We selected Wuxi, a typical developed city of eastern China, collected and tested the contents of heavy metals in the urban soils of Wuxi in May 2020. Combined with Pb isotope analysis, ecological and health risk asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Among them, OsHMP37 had a much higher expression level than the other seven HMPs, whereas OsHMP28 was solely expressed in the roots. Only OsHMP09, OsHMP18, and OsHMP22 showed increased expression levels in all tissues, despite the fact that most of the selected OsHMPs were variably expressed in different tissues under varying HM exposures [45]. Approximately 43 putative Fe-S cluster assembly genes have also been identified in the rice (Oryza sativa) genome and the expression of all genes has been validated [59,60].…”
Section: Role Of Hm Transporters (Hmts) and Tolerant Proteins (Hmps)mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, OsHMP37 had a much higher expression level than the other seven HMPs, whereas OsHMP28 was solely expressed in the roots. Only OsHMP09, OsHMP18, and OsHMP22 showed increased expression levels in all tissues, despite the fact that most of the selected OsHMPs were variably expressed in different tissues under varying HM exposures [45]. Approximately 43 putative Fe-S cluster assembly genes have also been identified in the rice (Oryza sativa) genome and the expression of all genes has been validated [59,60].…”
Section: Role Of Hm Transporters (Hmts) and Tolerant Proteins (Hmps)mentioning
confidence: 99%
“…An extensive study in eastern China investigated HM levels in urban soils and found that high concentrations of HMs in soil were mainly concentrated in central and western regions with relatively few spatial variations [45]. Municipal solid waste, automobile emissions, combustion of coal, and HM emissions from human activities including vehicle exhaust are all partially responsible for the rise of lead isotopes in urban soils.…”
Section: Natural and Anthropogenic Sources Of Hm Toxicity In Ricementioning
confidence: 99%
“…33 This index combines ecology, biochemistry, and other aspects to evaluate the potential ecological hazard of heavy metals. 34 This index is calculated as eqn (7), where EI i is the single potential ecological risk index of heavy metal i, C i is the concentration of heavy metal i, S i is the environmental quality standard of heavy metal i, and T i is the toxicity coefficient of heavy metal i. In this study, the background values of the studied heavy metals were used as the quality standard, and the toxicity coefficients of each heavy metal were Co = 5, Cr = 2, Cu = 5, Mn = 1, Ni = 5, Pb = 5, Zn = 1, and Cd = 30.…”
Section: Potential Ecological Risk Index (Ri)mentioning
confidence: 99%
“…Heavy metal is one of the most toxic species which exists widely in soil and is closely related to human health [ 31 ]. The heavy metals in soil can further enter drink water and plants, and then enter the human body by diet.…”
Section: Sequential Speciation Analysis Of Heavy Metals In Soil Samplesmentioning
confidence: 99%